PERKEMBANGAN PERMUKIMAN DIPERKOTAAN Studi tentang Dampak Perkembangan Permukiman Terhadap Kehidupan Sosial Keagamaan di Kota Palopo - Badruzzaman Badruzzaman (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This Writing is a conclucion of research, that was conducted in Palopo.This study aims to describe the model of settlement and its implication tosocial relationship. Data was collected using interview, observation,and documentation. Data was analized using qualitative method.This study indicates that model of social settlement at Palopo is segregatedpluralism, based on social stratification, etnic, and occupation.This implicates to social problem, such as social distance, social distortion,drugs, and prostitution